The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3832/ifor3531-014
|View full text |Cite
|
Sign up to set email alerts
|

Determination of differences in temperature regimes on healthy and bark-beetle colonised spruce trees using a handheld thermal camera

Abstract: Biogeosciences and ForestryBiogeosciences and Forestry Determination of differences in temperature regimes on healthy and bark-beetle colonised spruce trees using a handheld thermal camera Andrej Majdák (1) , Rastislav Jakuš (1-2) , Miroslav Blaženec (1) In this study, we compared the daily temperature regimes of healthy uninfected trees in the interior of a forest stand and at the fresh forest edge with infested trees at the forest edge in an area affected by a bark beetle outbreak. We estimated the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, the average difference compared to the intact trees was only about 0.4 • C, which is below the sensitivity threshold of the sensors. A study by Majdák et al (2021) reported using an infrared-based thermo-camera to distinguish infested trees on forest edges. They found a significant difference in bark surface temperature (reaching tens of • C) only on the sun-exposed side of infested trees on days when air temperature reached 34 • C and bark surface temperature was nearly 60 • C. The temperature difference on the shaded side was lower, and on colder days (maximum air temperature of 24 • C), it was not significant, which corresponds with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the average difference compared to the intact trees was only about 0.4 • C, which is below the sensitivity threshold of the sensors. A study by Majdák et al (2021) reported using an infrared-based thermo-camera to distinguish infested trees on forest edges. They found a significant difference in bark surface temperature (reaching tens of • C) only on the sun-exposed side of infested trees on days when air temperature reached 34 • C and bark surface temperature was nearly 60 • C. The temperature difference on the shaded side was lower, and on colder days (maximum air temperature of 24 • C), it was not significant, which corresponds with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (Majdák et al, 2021) reported a measurable increase in bark surface temperature following bark beetle infestation in sun-exposed trees on the forest edge. These trees were weakened by infestation and could not keep the optimal temperature.…”
Section: Introductionmentioning
confidence: 89%
“…Imaging-based methods involve the use of optical sensors such as thermal imaging sensors, HMI (hyperspectral or multispectral imaging) sensors or LiDAR (Light Detection and Ranging). Thermal imaging is based on IR (InfraRed) radiation emitted from materials and it is mainly used to (i) measure cavities and physical damages in the living wood [29], [30], (ii) detect infections caused by insects and bacteria [31], [32], and (iii) calculate water stress levels by measuring the temperature of the leaves in the canopy [14]. On the other hand, HMI sensors capture various bands in the electromagnetic spectrum, usually near-infrared and parts of the visible spectrum.…”
Section: Related Workmentioning
confidence: 99%
“…However, note that the temperature expansion coefficient is usually determined for dry wood (5−15% moisture content) with no such coefficients existing for moist, live tree stems, including bark. As such, a 10 • C change in air temperature results in a smaller temperature change in the stem because the sap transported in the wood cools the stem during the day (Majdak et al, 2021). Furthermore, any size changes due to temperature affecting the wood deeper in the stem than the anchoring of the dendrometer takes place (about 5−10 cm in the case of the dendrometers used in TreeNet) is likely irrelevant as the dendrometer reading is not affected.…”
Section: Potential Inadequacies Associated With Dendrometer Datamentioning
confidence: 99%